Senseless - Cole, Steve (Scotland: Barrington Stoke, Edinburgh, 2017)
It's a dream come true - Kenzie has been invited to a big international gaming tournament on a sun-soaked island. But then unreality ratchets up with disturbing scenes involving other contestants, soldiers and frantic chases through the hotel. Worst of all, Kenzie seems to be losing his senses one by one - and he has no idea whether the dangers he faces are real or the game
Keywords: Children's stories